2014
DOI: 10.2215/cjn.07460713
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Handling with Dual Renin-Angiotensin System Inhibition in Diabetic Nephropathy

Abstract: SummaryBackground and objectives Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers are the cornerstones of pharmacologic therapy in diabetic nephropathy. Mineralocorticoid receptor blockers reduce proteinuria as single agents or add-on therapy to other renin-angiotensin-aldosterone system-inhibiting drugs in these patients. The long-term benefits and ultimate role of mineralocorticoid receptor blockers in diabetic nephropathy remain unknown. A clinical trial previously showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Interestingly, angiotensin signaling appeared to play a permissive role for potassium secretion, since treatment with losartan rendered the mice unable to handle moderate dietary potassium [88]. This is consistent with clinical data showing that dual RAAS blockade raises serum potassium more than single RAAS blockade [89, 78]. The aldosterone synthase knockout study also found that colonic potassium secretion was entirely aldosterone-dependent [88], consistent with clinical data showing that hyperkalemia complicates the use of eplerenone in patients on hemodialysis [90].…”
Section: Potassium: Foe – Deleterious Effects Of Potassium Excesssupporting
confidence: 56%
“…Interestingly, angiotensin signaling appeared to play a permissive role for potassium secretion, since treatment with losartan rendered the mice unable to handle moderate dietary potassium [88]. This is consistent with clinical data showing that dual RAAS blockade raises serum potassium more than single RAAS blockade [89, 78]. The aldosterone synthase knockout study also found that colonic potassium secretion was entirely aldosterone-dependent [88], consistent with clinical data showing that hyperkalemia complicates the use of eplerenone in patients on hemodialysis [90].…”
Section: Potassium: Foe – Deleterious Effects Of Potassium Excesssupporting
confidence: 56%
“…From a total of 236 potentially eligible studies, 220 were excluded because they were not relevant to the study objectives; were reviews, meeting abstracts, case-only studies (ie, a control group [in which control medication or placebo was added to standard AD/RP/AHT treatment] was not included); or contained no detailed, usable data necessary for the meta-analysis. A total of 16 studies 23,28,34,35,[42][43][44][45][46][47][48][49][50][51][52][53] were included in the present metaanalysis and are described in the table (see also Supplemental Tables 1A-3B in the online version 28,34,43,45,47,49,52,53 ; and hyperkalemia, 12 studies (spironolactone, 319; control, 295). 28,34,35,[43][44][45][46]48,49,50,52,53 Effects of the Addition of Spironolactone on Urinary Protein/Albumin Excretion Compared with controls, the addition of spironolactone to standard AD/RP/AHT treatment significantly reduced end-of-treatment 24-hour urinary albumin/protein excretion (MD = -61.48; 95% CI, -96.74 to -26.23; P = 0.0006) (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…Loop or thiazide diuretics have not been shown to be beneficial. Mineralocorticoid receptor blockers decrease risk, but in the work by Mehdi et al (44), the addition of spironolactone to 80 mg lisinopril in patients with diabetes and proteinuria significantly decreased proteinuria but caused hyperkalemia .6 mEq/L in 50% of individuals (44,45). Lower BP may be beneficial in individuals with proteinuria (46).…”
Section: Why Is the Evidence Not Sufficient For Albuminuria?mentioning
confidence: 99%